Driving in the fasting month of Ramadan: An observational study on speeding, horn honking, and using seat belts. (October 2016) - Yıldırım-Yenier, Zümrüt; Lajunen, Timo; Özkan, Türker
Highlights: Speeding, horn honking, and not using seat belt were prevalent both in Ramadan and non-Ramadan. Mean speed was lower, honked horns were higher, and seat belt use was lower in Ramadan as compared to non-Ramadan. Findings overall showed that Ramadan had a limited role on speeding, horn honking, and seat belt use. Abstract: The aim of this study was to examine how Ramadan, i.e., fasting month for believers of Islam, was associated to observable driving behaviours (i.e., speeding, horn honking, and using seat belts) as compared to non-Ramadan. Observations on speeding, horn honking, and using seat belts were held during and after Ramadan in different times of the day in the same region of the city of Ankara. Speeds of 1885 vehicles were measured by hand held radar on a two-way eight-lane road with a 50 km/h speed limit. Horn honking was recorded at a signalised intersection with a hidden camera when the light turned into green in terms of 510 traffic light cycles. Seat belt wearing of 2106 drivers was observed at the same intersection. Findings indicated that (a) mean speed was lower, (b) honked horns were higher, and (c) seat belt use was lower in Ramadan as compared to non-Ramadan, though each negative driving behaviour was prevalent in both periods. Thus this study showed that the Ramadan period had a limited role on speeding, horn honking, and using seat belts.